Analisis Usability Aplikasi Sambara dengan Metode System Usability Scale dan USE Questionnaire - Felicia Felicia; Aini Suri Talita; Naeli Umniati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Samsat Mobile Jawa Barat (Sambara) is an Android-based application developed by the West Java provincial government to check vehicle taxes in West Java. This study aims to measure the usability of the Sambara application using the System Usability Scale (SUS) and USE Questionnaire methods. The SUS and USE Questionnaire methods are questionnaire-based methods with 10 and 30 questions. The study involved 42 respondents. The results of the validity test show that all data are valid so that they can be used for the research. The results of data processing with the SUS method showed an average value of 62.91. This value is categorized as OK with Grade C-, Percentile Rank 35%, Marginal Acceptability, and Passive NPS. This means that the Sambara application can be accepted by the community in marginal groups with passive users; users do not recommend the application to others. The results of data processing using the USE Questionnaire method obtained an average value of 76.1%, which means that the Sambara application is considered suitable for use. The average value of the questionnaire results is 5.32 out of 7. It means that usability of Sambara application is considered good.